Heat pump at subsoil water for heat and potable water supply - Denysova, Alla Evseevna; Mazurenko, Anton Stanislavovych; Denysova, Anastasiia Sergiivna (НТУ "ХПІ", 2017)
Removal of groundwater with further use of it for potable water supply and heat supply with the use of heat pump is an important problem. A new revolutionary approach to the decision of energy and water saving that provides rational accommodation of groundwater boreholes ensuring the required flow rate of water through the heat pump evaporator with simultaneously high intensity of heat exchange process is proposed. The method of calculation which allows determining the necessary depth of borehole, quantity of boreholes, in consideration of flow rate and temperature of subsoil water determining capacity of heat pump installation is worked out. Realization and algorithm of calculation of subsoil water heat pump installation are developed. Results that confirms efficiency of its work for heat and water supply simultaneously are shown on concrete example.

Запропоновано новий підхід до вирішення проблеми видалення ґрунтових вод з подальшим їх використанням на базі теплового насоса для цілей теплопостачання та забезпечення питною водою. Розроблено методику розрахунку, що дозволяє визначити, виходячи із заданої потужності теплового насоса, глибину свердловини, кількість свердловин, з урахуванням швидкості і температури ґрунтових вод. Розроблено алгоритм розрахунку установки, реалізація якої показана на конкретному прикладі, що підтверджує її ефективність для забезпечення споживачів одночасно опаленням, питною водою, а також для запобігання підтоплення будинків ґрунтовими водами.
Тепловий насос з використанням ґрунтових вод для теплозабезпечення та постачання питною водою
Keywords: heat pump; subsoil water; heat supply; potable water supply; тепловий насос; теплопостачання; водопостачання; ґрунтові води